2019
DOI: 10.1128/mbio.00377-19
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of the Motility Machinery in Halophilic Archaea

Abstract: Bacteria and archaea exhibit tactical behavior and can move up and down chemical gradients. This tactical behavior relies on a motility structure, which is guided by a chemosensory system. Environmental signals are sensed by membrane-inserted chemosensory receptors that are organized in large ordered arrays. While the cellular positioning of the chemotaxis machinery and that of the flagellum have been studied in detail in bacteria, we have little knowledge about the localization of such macromolecular assembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(129 citation statements)
references
References 72 publications
(130 reference statements)
13
116
0
Order By: Relevance
“…Live imaging is essential for the understanding of complex dynamic cellular events, such as changes in cell shape, cell division and DNA segregation. Despite such methods being well-established in bacteria and eukaryotes, live imaging has only recently been applied to the study of cell biological processes in archaea [1], where imaging of halophilic archaea has led to surprising new findings [2][3][4][5]. Live imaging of archaea remains challenging, especially when compared to bacteria, because archaea tend to be mechanically soft and several representatives are extremophiles, necessitating the development of novel techniques [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Live imaging is essential for the understanding of complex dynamic cellular events, such as changes in cell shape, cell division and DNA segregation. Despite such methods being well-established in bacteria and eukaryotes, live imaging has only recently been applied to the study of cell biological processes in archaea [1], where imaging of halophilic archaea has led to surprising new findings [2][3][4][5]. Live imaging of archaea remains challenging, especially when compared to bacteria, because archaea tend to be mechanically soft and several representatives are extremophiles, necessitating the development of novel techniques [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…This evidence is even more striking for coccoid bacteria, for which a single point mutation in FtsZ is able to induce cell elongation in Staphylococcus aureus (31). However, haloarchaea might have conserved at least two distinct elongation modes in addition to cell division, generating disk-like and rod-like populations (32). This scenario would also corroborate the morphological malleability of haloarchaea, being capable of assuming unusual shapes like triangles and squares (33,34).…”
Section: Discussionmentioning
confidence: 91%
“…To assess if ParA/MinD homologs in archaea play a role in cellular positioning, we selected the model archaeon Haloferax volcanii, which has genetic tools and fluorescent fusion proteins available to address questions relating to intracellular organization. Recent work in H. volcanii has indicated that positioning of the motility structure, chemosensory arrays and cell division machinery is regulated by unknown mechanisms [43][44][45] . H. volcanii cells display different shapes dependent on the growth stage of the culture 43,44,46 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in H. volcanii has indicated that positioning of the motility structure, chemosensory arrays and cell division machinery is regulated by unknown mechanisms [43][44][45] . H. volcanii cells display different shapes dependent on the growth stage of the culture 43,44,46 . Cells in early log-phase are rod-shaped and motile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation